As representações do caipira: o discurso da/na música sertaneja raiz - Terra, Rosana Ferreira (2007)
Caipira music, or the call root Sertaneja music, is heard and/or admired for a few people. This fact occurs due the crystallized image that the society, mainly in the urban zone, has of the countryside man, which it is still seen, in the present, as a caricature. This fact can be seen in the representation of the caipira Nerso da Capitinga in the TV program Zorra Total, of Rede Globo (TV company). Therefore, the objective of this research is to reflect about this representation of the countryside man, rescuing cultural and social elements that had allowed that this image was crystallized from a pejorative and caricatured form. For this, it was used the French branch of Discourse Analysis (DA) underlining the concepts of discursive formations, ideological formations and discursive memory.